Patients’ perception of the pharmacovigilance system: A pre-diagnostic and post-interventional cross-sectional survey - Rehman, Atta Ur; Khalid, Samina Naeem; Zakar, Rubeena; Hani, Ume; Zakria Zakar, Muhammad; Fischer, Florian (Frontiers in Pharmacology, 2022)
Background & Objective The risk of adverse reactions necessitated the pharmacovigilance system for patient safety. Literature search documented better health literacy of patients through intervention. This investigation aims to assess the perception and the effect of an intervention on patients regarding adverse reactions caused by drugs. Methods A pre-diagnostic and post-interventional cross-sectional investigation was designed with sample size of 423 patients in hospitals of Islamabad. The proportion of patients was selected based on a stratified probability technique. A prevalidated tool was used to collect the response twice through health promotion brochure with counseling was applied as an intervention. Results The outcome of the investigation revealed that prerequisite of the pharmacovigilance center in the hospital among respondents was improved significantly by 41.2% after intervention. Knowledge, communication, and practice was significantly different with respect to gender. There was a moderate Pearson correlation between diagnostic and interventional responses of patient’s knowledge of adverse reactions by drugs(r=0.66, p<0.01), patient’s communication in pharmacovigilance. (r=0.62, p<0.01) and a strong correlation between diagnostic and interventional response of patient's practice in the pharmacovigilance system(r=0.72, p<0.01). Paired t-test statistics showed significant differences among all variables. Conclusion The finding of the investigation provided evidence that patient awareness significantly improved by the health promotion model. Patient participation in the reporting of adverse reactions of drugs will complement the hospital staff reporting. These reports will construct an authentic cross-checked database for rational drug safety practices in Pakistan. Keywords: Patients, Perception, Pharmacovigilance, Health promotion, Intervention